PENGARUH SISTEM PENGENDALIAN INTERNAL DAN ASIMETRI INFORMASI TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI SERTA DAMPAKNYA TERHADAP KUALITAS LAPORAN KEUANGAN - Nurhayati Nurhayati; Puji Muniarty (Sekolah Tinggi Ilmu Ekonomi AMM, 2018)
This study aims to examine the influence of internal control systems and information asymmetry on the tendency of accounting fraud and it’s implications on the quality of financial statements at PT. Telkomsel Bima Branch. The population of this research is all employees at PT. Telkomsel Bima Branch that is 57 people. Technic of sample interpretation was done with purposive sampling toward 48 respondents who were employees directly involved in financial management, planning, preparing financial report and billing. The instrument of data analysis used Smart PLS 3.0. The results of the research showed that the internal control system has a negative and insignificant effect on the tendency of accounting fraud, while information asymmetry has a positive and significant effect on the tendency of accounting fraud. Furthermore, the tendency of accounting fraud has a negative and significant effect on the quality of financial statements.